2019
DOI: 10.2138/am-2019-6766
|View full text |Cite
|
Sign up to set email alerts
|

A XANES and EPMA study of Fe3+ in chlorite: Importance of oxychlorite and implications for cation site distribution and thermobarometry

Abstract: Chlorite is a ubiquitous product of metamorphism, alteration of magmatic rocks and hydrothermal processes owing to its large stability field and wide compositional range. Its composition is governed by several substitutions and has been used as a geothermometer, on the basis of empirical, semi-empirical, and thermodynamic models. As in some other phyllosilicates of petrological interest, the oxidation state of iron in chlorite may differ from the usually assumed divalent state. However, the crystal chemistry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…Crystallization temperature calculated with the chlorite thermometers of Vidal et al () and Bourdelle et al () are reported in Figure a, and range between 180 and 350°C. The minimum content of X Fe 3+ in chlorite calculated with the method of Vidal et al () ranges between 0.1 and 0.55, which is realistic for low‐ T chlorite (Masci et al, ). The entire iron content was considered divalent for the thermometer of Bourdelle et al (), as recommended in that study.…”
Section: Resultsmentioning
confidence: 99%
“…Crystallization temperature calculated with the chlorite thermometers of Vidal et al () and Bourdelle et al () are reported in Figure a, and range between 180 and 350°C. The minimum content of X Fe 3+ in chlorite calculated with the method of Vidal et al () ranges between 0.1 and 0.55, which is realistic for low‐ T chlorite (Masci et al, ). The entire iron content was considered divalent for the thermometer of Bourdelle et al (), as recommended in that study.…”
Section: Resultsmentioning
confidence: 99%
“…The most remarkable cationic substitutions occurring in chlorites are, therefore, as follows: All these cationic substitutions can be combined to form a multitude of exchange vectors. Additional substitutions can also be examined, such as the "hydroxyl" substitution and the deprotonation process, written Fe 3+ + 2OH − = Fe 3+ + O 2− + OH − and Fe 2+ + H + = Fe 3+ , respectively [11,16] (see Section 5). Consequently, octahedral sheets can theoretically exhibit three out of three occupied cationic sites (tri-tri octahedral structure; clinochlore, daphnite), two out of three occupied cationic sites (di-dioctahedral structure; dombassite), or one or other combination of these configurations, i.e., two out of three sites occupied for M1(M2) 2 and three out of three sites occupied for (M3) 2 M4 (di-trioctahedral structure, sudoite), or the opposite (tri-dioctahedral structure) [17,18].…”
Section: Compositional Variability Of Chloritesmentioning
confidence: 99%
“…Cationic substitutions where Fe 3+ is implicated can also be redefined. Masci et al [16] investigated a wide range of chlorite compositions by XANES and EMP, and claimed that the DT substitution implicating Fe 3+ is an artefact. This substitution is usually considered as the result of the combination of the Al-DT substitution and AF exchange but without the intervention of Al.…”
Section: Perspectives Of New Analytical and Thermometric Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synchrotron's advantages in spatial coherence (Eastwood et al, 2015;Zhu et al, 2010), monochromaticity (Torikoshi et al, 2003) and, subsequently, compositional and chemical sensitivities (Kao et al, 2013; collectively open vast scientific opportunities. One of the most popular approaches is to combine X-ray tomography with X-ray absorption spectroscopy (Yang et al, 2014(Yang et al, , 2019Yu, Farmand et al, 2018;Hitchcock, 2015;Masci et al, 2019;Nelson et al, 2011;Zhang et al, 2020;Zhu et al, 2020;Wang et al, 2016), featuring a much desired experimental capability that could spatially resolve chemical heterogeneity by probing ISSN 1600-5775 # 2021 International Union of Crystallography spatially resolved X-ray spectroscopic signals. This is because the structural and chemical heterogeneities are not only ubiquitous in real-world functional materials but also are often interdependent, complicating the material system while also providing an opportunity for advanced functional materials engineering.…”
Section: Introductionmentioning
confidence: 99%